Travaux d'aiguille et mobilisation féminine : des plaines de l'Utah aux Nations Unies - Trigeaud, Sophie-Hélène (Anthropologica, 2013)
Common sense pushes needlework back to a formal traditional world, where women's activities are set apart from the men's world, a severance that contributes to women's vul nerability. In this ideology, it is assumed that, to attain eman cipation, women should give up traditional practices and adopt those of the dominant gender. This assumption brings up an issue evocative of Andersen's allegory: must the siren renounce her voice to adopt a form that will allow for her coexistence with man? We review a variety of research to study the socioan thropological meaning of sewing for women in various contexts. We will see that, far from being instruments of oppression, thé thread and needle can open up to expression and development.